A Testament of Sindh : Ethnic and Religious Extremism a Perspective - Korejo, M. S. (Muhammad Soaleh), 1923- (Karachi, Pakistan Oxford University Press, 2002)
Among the problems facing Sindh today, ethnic militarism, sectarian extremism, and political terrorism have acquired menacing proportions. The book is an attempt to seriously and frankly analyse the current problems of Sindh.
Include Appendix, Bibliography and Index
Keywords: Pakistan--Sindh -- Politics and government -- Communalism -- Ethnic relations -- Islam and politics